The association between leisure activity patterns and the prevalence of mild cognitive impairment in community-dwelling older adults - Zhang, Yuanyuan; Yang, Xinxin; Guo, Linlin; Xu, Xinyi; Chen, Bingyu; Ma, Xiaowei; Li, Yan (Frontiers in Psychology, 2023)
Objectives The study aimed to identify leisure activity patterns among older adults and explore the differences in the prevalence of mild cognitive impairment (MCI) of these patterns. Methods A total of 352 older adults aged ≥ 65 years in Shijiazhuang were enrolled in this study from June to September 2021. Their leisure activities and cognition were evaluated. Latent class analysis and logistic regression models were used for analysis. The manuscript was organized according to the STROBE guidelines. Results We identified three latent classes of leisure activities: multidomain activities (MDA) class (55%), self-improvement activities (SIA) class (21%), and family-centered activities (FCA) class (24%). Three latent classes significantly differed in general characteristics (gender, education, and body mass index) and the prevalence of MCI. The prevalence of MCI was 3.694 times higher in older adults in the FCA class than in older adults in the MDA class (OR = 3.694, P < 0.001) and 2.573 times higher in older adults in the SIA class (OR = 2.573, P = 0.036). Conclusion Patterns of low participation in intellectual activities were associated with MCI. Identifying the heterogeneity in leisure activity engagement in later life was critical for tailoring interventions and designing programs that can improve the cognitive function of older adults.